Oncolytic virotherapy for metastatic breast cancer – a case report - Gesundheit, Benjamin; Muckenhuber, Alexander; Posen, Yehudit; Ellis, Ronald; Zisman, Philip David; Schmoll, Harald; Weisslein, Christine; Srinivas Raju, Jayadeepa (Frontiers in Oncology, 2023)
Background: Breast cancer is one of the most common malignancies worldwide and remains incurable after metastasis, with a 3-year overall survival rate <40%. Case Presentation: A 40-year-old, Caucasian patient with a grade-3 estrogen receptor-, progesterone receptor-, Her2-positive breast tumor and two lung nodules was treated with intramuscular targeted immunotherapy with trastuzumab and oral tamoxifen hormone therapy, together with customized intra-tumoral oncolytic virotherapy (IT-OV) over a 17-month period. PET/CT imaging at 3 and 6 months showed increased primary tumor size and metabolic glucose uptake in the primary tumor, axillary lymph nodes and lung nodules, which were paralleled by a hyperimmune reaction in the bones, liver, and spleen. Thereafter, there was a steady decline in both tumor size and metabolic activity until no radiographic evidence of disease was observed. The treatment regimen was well tolerated with a good quality of life throughout. Conclusion: Integration of IT-OV immunotherapy in standard treatment protocols presents an attractive modality for late-stage primary tumors with an abscopal effect on metastases.